GREEN MARKETING, CSR, AND GREEN LIFESTYLE ON WULING EV GREEN PURCHASE INTENTION: THE MEDIATING ROLE OF GREEN BRAND IMAGE - Salma Barkah; Jasmine Farhan; Bambang Eko Samiono (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the influence of Green Marketing, CorporateSocialResponsibility (CSR), and Green Lifestyle on Green Purchase Intention throughGreenBrand Image as a mediating variable among individuals considering the purchaseof theirfirst Wuling electric vehicle in Jakarta. The analysis focuses on individuals in Jakarta who are considering buying a Wuling EV for the first time. This research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Data were collected through questionnaires distributed to 150 respondents who met the research criteria. The results indicate that Green Marketing, CSR, and Green Lifestyle do not have a significant direct effect on Green Purchase Intention. However, Green Brand Image has a positive and significant effect on Green Purchase Intention. Furthermore, Green Marketing, CSR, and Green Lifestyle significantly influence Green Brand Image. The mediation analysis reveals that Green Brand Image significantly mediates the effects of Green Marketing, CSR, and Green Lifestyle on Green Purchase Intention. These findings suggest that a strong green brand image plays a crucial role in increasing consumers’ intention to purchase Wuling electric vehicles. Therefore, these findings may provide insights for companies in developing green marketing initiatives, CSR programs, and environmental lifestyle campaigns to strengthen Green Brand Image and enhance Green Purchase Intention.